Reactive strength index scores correlate with game performance in female collegiate level volleyball players (Journal of Athletic Enhancement, 2022)
Objective: The reactive strength index (RSI) is a reliable and valid measure used by coaches to assess an athlete`s explosiveness. Despite its use, there is paucity in the research regarding normative data or correlational data between RSI scores and in-season game statistics for female collegiate level volleyball (VB) players. The first purpose of this study was to report RSI data for female collegiate level VB players. The second purpose of this study was to identify correlations between preseason RSI scores and game statistics.